2005
DOI: 10.1038/modpathol.3800393
|View full text |Cite
|
Sign up to set email alerts
|

Maspin expression in CIN 3, microinvasive squamous cell carcinoma, and invasive squamous cell carcinoma of the uterine cervix

Abstract: Maspin is a serine protease inhibitor with tumor suppression activity. It is expressed in normal breast and prostate tissue but is downregulated or absent in breast and prostate tumors. Recent reports have shown that decreased expression is associated with a greater propensity for metastasis in oral squamous cell carcinomas. We know that some high-grade cervical intraepithelial neoplasia progress to invasive carcinomas while others either persist at the same degree of atypia or regress. The pattern of maspin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Further immunohistochemical analysis indicated maspin expression was positively correlated with lymph node metastasis, in line with our results [29]. However, many articles have described a negative association between maspin expression and carcinoma progression in several malignancies, including those of the breast, prostate, colon, bladder, uterine cervix, and even stomach [8,17,[25][26][27][30][31][32]. These contradictory results might derive from specific regulation in different organs or the different genetic backgrounds of the populations studied, although definite evidence for a paradoxical mechanism remains elusive.…”
Section: Discussionsupporting
confidence: 90%
“…Further immunohistochemical analysis indicated maspin expression was positively correlated with lymph node metastasis, in line with our results [29]. However, many articles have described a negative association between maspin expression and carcinoma progression in several malignancies, including those of the breast, prostate, colon, bladder, uterine cervix, and even stomach [8,17,[25][26][27][30][31][32]. These contradictory results might derive from specific regulation in different organs or the different genetic backgrounds of the populations studied, although definite evidence for a paradoxical mechanism remains elusive.…”
Section: Discussionsupporting
confidence: 90%
“…30 A significant decrease of maspin between cervical intraepithelial neoplasia versus invasive squamous cell carcinoma and between microinvasive squamous cell carcinoma versus invasive squamous cell carcinoma has been reported. 7 Also, a decrease of the maspin expression in the following sequence has been described: normal breast tissue, ductal carcinoma in situ, invasive breast cancer, node metastases. 3 These facts point to a likely role of maspin in progression from in situ to invasive carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…2 These conflicting results could be attributable in part to a lack of an exact quantification of the maspin expression 23 MASPIN AND ORAL CANCER / Iezzi et al or to a variation in pathogenesis of the cancers of different organs. 7 Also, the localization of maspin positivity seems to play a relevant role in determining the patient prognosis. 2 An enhanced nuclear expression is associated with a favorable prognosis, whereas an enhanced cytoplasmic expression is associated with poor prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…TOXICOLOGIC PATHOLOGY penetrating lesions in the present study demonstrated less expression of maspin. In general, loss of maspin was correlated with poor prognosis in colon, uterus, breast, prostate, skin, thyroid, and oral SCC (Amir et al 2005;Bettstetter et al 2005;Biliran and Sheng 2001;Denk et al 2007;Shams et al 2006;Xu et al 2005;Yin et al 2006;Yoshizawa et al 2009b;Xia et al 2000;Yasumatsu et al 2001). a-Smooth muscle actin and SPARC were not a prominent feature of the stroma adjacent to TCAB-induced SCC.…”
Section: Discussionmentioning
confidence: 99%